Micromodels for the in-plane failure analysis of masonry walls: Limit Analysis, FEM and FEM/DEM approaches - Marco Pepe; Marco Pingaro; Patrizia Trovalusci; Emanuele Reccia; Lorenzo Leonetti (Fracture and Structural Integrity)
In the last decades the modeling of masonry structures has become an argument particularly appealing for many researchers and a large variety of numerical techniques have been formulated with the aim to produce practical applications in civil engineering, with special reference to the preservation and restoration of cultural heritage. Nevertheless, the question appears today still far from being resolved in a general way. The characteristics of frailty, heterogeneity and anisotropy of masonry, as well as the extreme variety of the building/construction rules strongly compromise the possibility of a unified description of its mechanical behavior.